Solve: $\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$.
Answer
Verified
457.2k+ views
Hint: The given second order differential equation has a function of x. So, this becomes a particular integral. As the function is trigonometrical, we assume the integral function as $y\left( x \right)=A\cos 3x+B\sin 3x$. We find the values of ${{D}^{2}}=\dfrac{{{d}^{2}}}{d{{x}^{2}}},D=\dfrac{d}{dx}$ and place them in the main equation. We get two equations of two unknowns A and B. we solve them to find the values of A and B.
Complete step by step answer:
We have been given a second order differential equation with constant coefficient.
$\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$. Here ${{D}^{2}}=\dfrac{{{d}^{2}}}{d{{x}^{2}}},D=\dfrac{d}{dx}$.
In this type of equation, we get the characteristics equation by taking the differential form of the equation.
We assume the solution of the differential equation. As the function of x is $f\left( x \right)=\cos 3x$. We take the PI as $y\left( x \right)=A\cos 3x+B\sin 3x$.
Here PI describes a particular integral which is the solution of the differential equation $\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$. First, we find out the PI differentiations.
We have $\left( {{D}^{2}}+4D+13 \right)y=\dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y$.
Differentiating both side of $y\left( x \right)=A\cos 3x+B\sin 3x$, we get
$\begin{align}
& y\left( x \right)=A\cos 3x+B\sin 3x \\
& \Rightarrow \dfrac{dy}{dx}=-3A\sin 3x+3B\cos 3x \\
\end{align}$
We differentiate again to find the value of $\dfrac{{{d}^{2}}y}{d{{x}^{2}}}$.
$\begin{align}
& \dfrac{dy}{dx}=-3A\sin 3x+3B\cos 3x \\
& \Rightarrow \dfrac{{{d}^{2}}y}{d{{x}^{2}}}=-9A\cos 3x-9B\sin 3x \\
\end{align}$
We put the values in the equation to get
$\begin{align}
& \dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y \\
& =\left( -9A\cos 3x-9B\sin 3x \right)+4\left( -3A\sin 3x+3B\cos 3x \right)+13\left( A\cos 3x+B\sin 3x \right) \\
& =\cos 3x\left( 4A+12B \right)+\sin 3x\left( 4B-12A \right) \\
\end{align}$
We have to satisfy the value of $\left( {{D}^{2}}+4D+13 \right)y=\dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y$ with $\cos 3x$.
We equate them to get two equations of two unknowns A and B.
$\cos 3x\left( 4A+12B \right)+\sin 3x\left( 4B-12A \right)=\cos 3x$.
The equations are $\left( 4A+12B \right)=1,\left( 4B-12A \right)=0$.
We multiply the first equation with 3 and add it to the second equation.
$\begin{align}
& 3\left( 4A+12B \right)=3,\left( 4B-12A \right)=0 \\
& \Rightarrow 12A+36B=3,4B-12A=0 \\
\end{align}$
Adding them we get
$\begin{align}
& \left( 12A+36B \right)+\left( 4B-12A \right)=3+0 \\
& \Rightarrow 40B=3 \\
& \Rightarrow B=\dfrac{3}{40} \\
\end{align}$
Putting value of B in one equation we get
$\begin{align}
& \left( 4A+12B \right)=1 \\
& \Rightarrow 4A+12\left( \dfrac{3}{40} \right)=1 \\
& \Rightarrow 4A=1-\dfrac{9}{10}=\dfrac{1}{10} \\
& \Rightarrow A=\dfrac{1}{40} \\
\end{align}$
We got values of both A and B.
Putting the values in $y\left( x \right)=A\cos 3x+B\sin 3x$ we get $y\left( x \right)=\dfrac{\cos 3x}{40}+\dfrac{3\sin 3x}{40}$.
Simplifying we get $40y=\cos 3x+3\sin 3x$. This is the solution of $\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$.
Note: We also can solve it by breaking it in two parts of CF and PI. Here CF defines the complementary function which is the solution of $\left( {{D}^{2}}+4D+13 \right)y=0$. Then we place the value of 3 in the particular integral. The final solution becomes $y\left( x \right)=CF+PI$.
Complete step by step answer:
We have been given a second order differential equation with constant coefficient.
$\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$. Here ${{D}^{2}}=\dfrac{{{d}^{2}}}{d{{x}^{2}}},D=\dfrac{d}{dx}$.
In this type of equation, we get the characteristics equation by taking the differential form of the equation.
We assume the solution of the differential equation. As the function of x is $f\left( x \right)=\cos 3x$. We take the PI as $y\left( x \right)=A\cos 3x+B\sin 3x$.
Here PI describes a particular integral which is the solution of the differential equation $\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$. First, we find out the PI differentiations.
We have $\left( {{D}^{2}}+4D+13 \right)y=\dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y$.
Differentiating both side of $y\left( x \right)=A\cos 3x+B\sin 3x$, we get
$\begin{align}
& y\left( x \right)=A\cos 3x+B\sin 3x \\
& \Rightarrow \dfrac{dy}{dx}=-3A\sin 3x+3B\cos 3x \\
\end{align}$
We differentiate again to find the value of $\dfrac{{{d}^{2}}y}{d{{x}^{2}}}$.
$\begin{align}
& \dfrac{dy}{dx}=-3A\sin 3x+3B\cos 3x \\
& \Rightarrow \dfrac{{{d}^{2}}y}{d{{x}^{2}}}=-9A\cos 3x-9B\sin 3x \\
\end{align}$
We put the values in the equation to get
$\begin{align}
& \dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y \\
& =\left( -9A\cos 3x-9B\sin 3x \right)+4\left( -3A\sin 3x+3B\cos 3x \right)+13\left( A\cos 3x+B\sin 3x \right) \\
& =\cos 3x\left( 4A+12B \right)+\sin 3x\left( 4B-12A \right) \\
\end{align}$
We have to satisfy the value of $\left( {{D}^{2}}+4D+13 \right)y=\dfrac{{{d}^{2}}y}{d{{x}^{2}}}+4\dfrac{dy}{dx}+13y$ with $\cos 3x$.
We equate them to get two equations of two unknowns A and B.
$\cos 3x\left( 4A+12B \right)+\sin 3x\left( 4B-12A \right)=\cos 3x$.
The equations are $\left( 4A+12B \right)=1,\left( 4B-12A \right)=0$.
We multiply the first equation with 3 and add it to the second equation.
$\begin{align}
& 3\left( 4A+12B \right)=3,\left( 4B-12A \right)=0 \\
& \Rightarrow 12A+36B=3,4B-12A=0 \\
\end{align}$
Adding them we get
$\begin{align}
& \left( 12A+36B \right)+\left( 4B-12A \right)=3+0 \\
& \Rightarrow 40B=3 \\
& \Rightarrow B=\dfrac{3}{40} \\
\end{align}$
Putting value of B in one equation we get
$\begin{align}
& \left( 4A+12B \right)=1 \\
& \Rightarrow 4A+12\left( \dfrac{3}{40} \right)=1 \\
& \Rightarrow 4A=1-\dfrac{9}{10}=\dfrac{1}{10} \\
& \Rightarrow A=\dfrac{1}{40} \\
\end{align}$
We got values of both A and B.
Putting the values in $y\left( x \right)=A\cos 3x+B\sin 3x$ we get $y\left( x \right)=\dfrac{\cos 3x}{40}+\dfrac{3\sin 3x}{40}$.
Simplifying we get $40y=\cos 3x+3\sin 3x$. This is the solution of $\left( {{D}^{2}}+4D+13 \right)y=\cos 3x$.
Note: We also can solve it by breaking it in two parts of CF and PI. Here CF defines the complementary function which is the solution of $\left( {{D}^{2}}+4D+13 \right)y=0$. Then we place the value of 3 in the particular integral. The final solution becomes $y\left( x \right)=CF+PI$.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
What are the major means of transport Explain each class 12 social science CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
Explain sex determination in humans with the help of class 12 biology CBSE
Explain with a neat labelled diagram the TS of mammalian class 12 biology CBSE
Distinguish between asexual and sexual reproduction class 12 biology CBSE
Explain Mendels Monohybrid Cross Give an example class 12 biology CBSE